Virtual Reality App (SI-VIGUR) to Improve Sleep Quality among Older Adults in Nursing Homes - Martini, Sri; Aguscik, Aguscik; Farama, Dodi Aflika; Somad, Abdul; Hartati, Sri (Indonesian Journal of Global Health Research, 2024)
Sleep disturbances are common among older adults, especially those residing in nursing homes, and can significantly affect their quality of life and overall well-being. Non-pharmacological interventions, such as guided imagery and virtual reality (VR), have shown promise in improving sleep quality by promoting relaxation and reducing cognitive arousal. The SI-VIGUR (Virtual Reality Guided Imagery) app combines VR technology with guided imagery to offer a therapeutic solution for improving sleep in older adults. This study aimed to evaluate the effectiveness of the SI-VIGUR VR app in improving sleep quality among older adults in nursing homes. This study aimed to evaluate the effectiveness of the Virtual Reality Guided Imagery (SI-VIGUR) application in improving sleep quality among older adults in nursing homes in Palembang City, South Sumatra, Indonesia, in 2024. Using a quasi-experimental design with pre- and post-tests, 80 participants aged 60 or older with sleep disturbances were selected. They received 15-minute SI-VIGUR sessions three times a week for 1 months. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Participants in the experimental group showed a significant improvement in sleep quality, as evidenced by a decrease in their PSQI scores (from 14.20 ± 1.86 to 7.31 ± 2.81). The intervention group demonstrated a marked reduction in poor sleep quality, with a higher percentage of individuals reporting fair or good sleep quality after the intervention compared to before. These findings were statistically significant (p = 0.0001), confirming the effectiveness of the SI-VIGUR app. The SI-VIGUR VR app proved to be an effective non-pharmacological intervention for improving sleep quality among older adults in nursing homes. The results suggest that VR-guided imagery can significantly reduce sleep disturbances, offering a promising solution for enhancing the well-being of older adults in institutional settings.